Pendampingan Pelaku UMKM dalam Memanfaatkan Platform Digital Di Era Society 5.0 untuk Peningkatan Kesejahteraan Ekonomi di Gampong Lam Duro - Silvia, Vivi; Humaira, Syifaan; Aziz, Nauval (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service aims to empower MSMEs in Gampong Lam Duro through the use of digital platforms in the Society 5.0 era. The background to this activity is the need for MSME players to adapt to technological developments in order to increase competitiveness and economic prosperity. This program is designed to provide basic education, training, and practical skills related to opportunities and strategies for using digital media. The implementation method involves three main stages: location observation and licensing, participant recruitment, and intensive training that includes pre-test and post-test to measure the effectiveness of the program. The training material includes an introduction to digital platforms, marketing strategies, and online store management. The results of the training showed an increase in participants' understanding by 40%, indicating success in providing knowledge and practical skills. In conclusion, this program is running well, having a positive impact on the ability of MSMEs to utilize digital media to support business development and economic prosperity.